Identification of trajectories of cardiac allograft vasculopathy after heart transplantation: a nationwide comparison. (25th November 2020) - Bonnet, G; Coutance, G; Van Keer, J; Raynaud, M; Aubert, O; Bories, M.C; Bruneval, P; Varnous, S; Leprince, P; Empana, J.P; Naesens, M; Patel, J.K; et al.
Abstract: Background: Cardiac allograft vasculopathy (CAV) is a major contributor of heart transplant recipient's mortality. However, little is known about CAV trajectories at a population level. Purpose: We aimed to identify the different profiles of CAV trajectories. Methods: Heart transplant recipients receiving care at 4 academic centers (2004 to 2016) were included. Patients underwent prospective, protocol-based monitoring consisting of repeated coronary angiographies together with systematic assessment of clinical, functional, histological and immunological parameters. The mainoutcome was the CAV trajectories, identified with unsupervised latent class mixed models. Results: Overall, 1, 301 patients were included (609 in France, 206 in Belgium and 486 in the US). The median follow-up post-transplant was 6.6 years (IQR=4.7) with 4, 710 coronary angiographies analyzed (3.6±1.6 CAV assessments per patient). In the French development cohort, we identified 4 distinct profiles of CAV trajectories over 10 years that were characterized by i) Patients without CAV at baseline and non-progression (n=317, 52.1%), ii) patients without CAV at baseline and late onset CAV progression (n=52, 8.5%), iii) patients with mild baseline CAV and mild progression (n=151, 24.8%), iv) patients with mild baseline CAV and accelerated CAV progression (n=89, 14.6%, discrimination 0.92). The 4 CAV trajectories were independently validated in the external validation cohorts from Belgium (discrimination=0.92) and the US (discrimination=0.97). Conclusion: In a large multicentric and highly phenotyped prospective cohort of heart transplant recipients, we identified and validated 4 distinct CAV trajectories corresponding to specific initial CAV grades and subsequent evolutions. Our results provide the basis for a trajectory-based assessment for risk stratification at early-stage post heart transplantation. Funding Acknowledgement: Type of funding source: None